1996
DOI: 10.2737/pnw-gtr-384
|View full text |Cite
|
Sign up to set email alerts
|

The Alexander Archipelago wolf: a conservation assessment.

Abstract: We summarized the scientific information available for the Alexander Archipelago wolf (Canis lupus ligoni) in the Tongass National Forest of southeast Alaska. Information concerning the morphology, distribution, taxonomy, genetics, and ecology of wolves are presented. Three issues for the conservation of wolves in southeast Alaska are discussed: loss of long-term carrying capacity for deer due primarily to extensive timber harvesting, increased mortality of wolves associated with improved human access from roa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(62 citation statements)
references
References 55 publications
2
53
0
Order By: Relevance
“…Keith (1981) and Marquard-Peterson (1998) suggested that when ungulate density and vulnerability vary, dierences in wolf diets are likely to occur. Wolf densities are generally higher where deer are abundant (Van Ballenberghe et al 1975;Weaver 1994; but see Peterson and Page 1988) and this pattern is evident on southeast Alaska islands (Person et al 1996). Moose and mountain goat are the primary ungulate prey on the coastal mainland (Fox and Streveler 1986) but kill rates for wolves (and wolf densities) tend to be lower where these species prevail (Carnes et al 1996;Dale et al 1995; but see Hayes 1995).…”
Section: Causes Of Stable Isotopic Variation Among Areasmentioning
confidence: 91%
See 3 more Smart Citations
“…Keith (1981) and Marquard-Peterson (1998) suggested that when ungulate density and vulnerability vary, dierences in wolf diets are likely to occur. Wolf densities are generally higher where deer are abundant (Van Ballenberghe et al 1975;Weaver 1994; but see Peterson and Page 1988) and this pattern is evident on southeast Alaska islands (Person et al 1996). Moose and mountain goat are the primary ungulate prey on the coastal mainland (Fox and Streveler 1986) but kill rates for wolves (and wolf densities) tend to be lower where these species prevail (Carnes et al 1996;Dale et al 1995; but see Hayes 1995).…”
Section: Causes Of Stable Isotopic Variation Among Areasmentioning
confidence: 91%
“…1). Because wolves occupy large home ranges (Person et al 1996) and the spatial distribution of salmon streams in southeast Alaska is rather uniform (Alaska Department of Fish and Game 1994), we assumed that southeast Alaska wolves had equal access to anadromous salmon throughout that area. On the other hand, deer densities dier markedly across the region.…”
Section: Sample Collection and Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…This Tongass old growth is critically important in the production of biological regulation (Person et al 1996), climate regulation (Leighty et al 2006), biodiversity refugia (e.g., Cotter and Kirchoff 2007), and numerous cultural and recreational services. Because it takes centuries to develop the biological characteristics of old growth, the management alternatives in the choice experiment offered the conservation of up to 445,000 acres of old growth scheduled for harvest (all old growth scheduled for harvest).…”
Section: Old-growth Conservationmentioning
confidence: 99%